2021
DOI: 10.1038/s41598-021-88942-w
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation capacity of cartilage is a critical factor in rate- and integrity-dependent fracture

Abstract: Articular cartilage heals poorly but experiences mechanically induced damage across a broad range of loading rates and matrix integrity. Because loading rates and matrix integrity affect cartilage mechanical responses due to poroviscoelastic relaxation mechanisms, their effects on cartilage failure are important for assessing and preventing failure. This paper investigated rate- and integrity-dependent crack nucleation in cartilage from pre- to post-relaxation timescales. Rate-dependent crack nucleation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Typical load, displacement, and time‐series raw data are obtained from microfracture experiments through the microindentation at slow and fast loading rates (Fig. 3B and 3C), which is consistent with a wider range of loading rates reported earlier by the authors (Han et al., 2021). Load‐versus‐displacement plots are obtained from the raw data and indicate the sudden drop in the load representing the first major point of fracture (Fig.…”
Section: Commentarysupporting
confidence: 88%
See 2 more Smart Citations
“…Typical load, displacement, and time‐series raw data are obtained from microfracture experiments through the microindentation at slow and fast loading rates (Fig. 3B and 3C), which is consistent with a wider range of loading rates reported earlier by the authors (Han et al., 2021). Load‐versus‐displacement plots are obtained from the raw data and indicate the sudden drop in the load representing the first major point of fracture (Fig.…”
Section: Commentarysupporting
confidence: 88%
“…Analysis of microfracture experiments has shown that less energy is required to nucleate microcracks under fast than under slow loading because of a shift from pre‐relaxation scale to post‐relaxation timescale (Han et al., 2019). Microfracture data can also be used to estimate cartilage toughness as a function of cartilage matrix integrity (Han et al., 2021). Under fatigue loading, load and displacement time‐series data can be analyzed (Fig.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Such measurements are connected with cartilage damage and PG content. 10,[41][42][43] Considering the fact that spiral DENSE MRI has a high penetration depth, it becomes an optimal method to measure viscoelastic behavior while easily tranferable to a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…This is because viscoelastic measurements need data acquisition with time which may require special methods not suitable for rapid physiolocal movements or in a clinical setting. On the other hand, spiral DENSE MRI captures high temporal resolution images that can measure not only creep behavoir but also other viscoelastic responses of the tissue including time-dependent deformation 10,41 and relaxation time 42,43 . Such measurements are connected with cartilage damage and PG content.…”
Section: Discussionmentioning
confidence: 99%